2009
DOI: 10.1111/j.1757-7861.2009.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between adolescent idiopathic scoliosis with double curve and polymorphisms of calmodulin1 gene/estrogen receptor‐α gene

Abstract: Objective: To investigate whether single nucleotide polymorphisms (SNP) of the calmodulin1 (CALM1) and estrogen receptor-a genes correlate with double curve in adolescent idiopathic scoliosis (AIS).Methods: A total of 67 Chinese patients with AIS with double curve and 100 healthy controls were recruited. Curve pattern and Cobb angle of each patient were recorded. The Cobb angle is at least 30°. There were 60 patients with Cobb angle Ն 40°. According to the apical location of the major curve, there were 40 thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
2
19
0
4
Order By: Relevance
“…Besides, Tang et al [16] demonstrated no association of XbaI polymorphism with occurrence, Cobb angle, or with anthropometric measurements in the Chinese Han population, which is consistent with Takahashi et al's research [17]. For ERa PvuII, one article [18] reported that ERa PvuII might be related to double curve in patients with adolescent idiopathic scoliosis (AIS). However, in four other studies in the Chinese or the Japanese population, the PvuII site polymorphism alone did not show any association with idiopathic scoliosis [12,[14][15][16].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Besides, Tang et al [16] demonstrated no association of XbaI polymorphism with occurrence, Cobb angle, or with anthropometric measurements in the Chinese Han population, which is consistent with Takahashi et al's research [17]. For ERa PvuII, one article [18] reported that ERa PvuII might be related to double curve in patients with adolescent idiopathic scoliosis (AIS). However, in four other studies in the Chinese or the Japanese population, the PvuII site polymorphism alone did not show any association with idiopathic scoliosis [12,[14][15][16].…”
Section: Introductionsupporting
confidence: 61%
“…There was a series of studies that looked into the association between the ERa XbaI A/G and ERa PvuII T/C polymorphisms and idiopathic scoliosis susceptibility; however, the results obtained were inconsistent or Table 1 General characteristics of studies included in the meta-analysis Products of PCR were genotyped by ABI3700 machine controversial [12][13][14][15][16][17][18]20]. To our knowledge, no metaanalysis has previously been published on the relationship between ERa XbaI A/G and ERa PvuII T/C polymorphisms and idiopathic scoliosis to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al postulated association of PvuII with double curve severe scoliosis in the Chinese population [18]. In three other studies the Chinese or the Japanese population, the PvuII site polymorphism alone did not show any association with IS [13], [15], [16].…”
Section: Introductionmentioning
confidence: 95%
“…Montanaro discovered that MATN1 single nucleotide polymorphism in 1p35 led to a disorder of chondrocyte distribution and caused scoliosis (61), whereas single nucleotide polymorphism at the Matrilin receptor level caused idiopathic scoliosis MTNR1B in 11q21-q22. Furthermore, an association between IS and Calmodulin1 (CALM1) gene polymorphisms has been reported (106). Esposito et al showed that steroid binding protein polymorphisms were effective in IS development (26).…”
Section: Genetic-hormonal Causesmentioning
confidence: 99%